Allosteric modulation of gonadotropin receptors - Lazzaretti, Clara; Simoni, Manuela; Casarini, Livio; Paradiso, Elia (Frontiers in Endocrinology, 2023)
Gonadotropins regulate reproductive functions by binding to G protein-coupled receptors (FSHR and LHCGR) expressed in the gonads. They activate multiple, cell-specific signalling pathways, consisting of ligand-dependent intracellular events. Signalling cascades may be modulated by synthetic compounds which bind allosteric sites of FSHR and LHCGR or by membrane receptor interactions. Despite the hormone binding to the orthosteric site, allosteric ligands and receptor heteromerizations may reshape intracellular signalling pattern. These molecules act as positive, negative or neutral allosteric modulators, as well as non-competitive or inverse agonist ligands, providing a set of new compounds of a different nature and with unique pharmacological characteristics. Gonadotropin receptor allosteric modulation is gathering increasing interest from the scientific community and may be potentially exploited for clinical purposes. This review summarizes the current knowledge on gonadotropin receptor allosteric modulation and their potential, clinical use.